2014
DOI: 10.1016/j.hlc.2014.05.006
|View full text |Cite
|
Sign up to set email alerts
|

Extracorporeal Membrane Oxygenation for Very High-risk Transcatheter Aortic Valve Implantation

Abstract: Background: Transcatheter aortic valve implantation (TAVI) can cause profound haemodynamic

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
26
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 49 publications
(28 citation statements)
references
References 14 publications
1
26
1
Order By: Relevance
“…Of those, 9 studies representing a total of 5191 patients met the inclusion criteria (Figure and Table 1). 8, 10, 11, 12, 13, 14, 15, 16, 17 All studies except the study by Seco et al15 were retrospective studies of institutional or national databases. All studies were published from 2012 to 2017, with 7 out of 9 studies published from the United States and Europe.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Of those, 9 studies representing a total of 5191 patients met the inclusion criteria (Figure and Table 1). 8, 10, 11, 12, 13, 14, 15, 16, 17 All studies except the study by Seco et al15 were retrospective studies of institutional or national databases. All studies were published from 2012 to 2017, with 7 out of 9 studies published from the United States and Europe.…”
Section: Resultsmentioning
confidence: 99%
“…The substudy of the PARTNER trial registry by Shreenivas et al was the largest study, contributing 109/203 (53.7%) patients, all of whom needed CPB 8. Commonly noted indications for CPB/VA‐ECMO included left ventricular (LV) or aortic annular rupture, rapid hemodynamic deterioration, severe aortic regurgitation, cardiac arrest from ventricular tachycardia or fibrillation, and obstruction of the left main coronary artery 8, 10, 11, 12, 13, 14, 15, 16, 17. The definition of hemodynamic deterioration varied across studies and included low cardiac output, need for high‐dose vasopressors and inotropes, prolonged pacing sequence, and severe LV dysfunction on echocardiography.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…A study of 100 trans-catheter aortic valve implantation (TAVI) patients, reported that anticipation for ECMO and institution of this mode of support prophylactically in the “high-risk” category on the EuroSCORE scale would potentially prevent the need for salvage VA ECMO, in a less optimal and controlled clinical setting, and carry better outcomes. In this study all-cause mortality occurred in none of the high-risk patients undergoing prophylactic VA ECMO (although p  > 0.05) [37]. …”
Section: Discussionmentioning
confidence: 99%
“…Finally, the observation that urgent conversion to surgery especially in high risk patients has worse outcome when is performed by sternotomy, supports the hypothesis that what we really need during a TAVR procedure is a left ventricular assist device for transient hemodynamic support, or a vascular surgeon for treating the possible vascular complications, and not necessarily a heart lung machine . The presence of left ventricular assist device instead of having a group of experts waiting as a safety net for a possible complication could possible decrease the overall cost of the process and could lead to proper and more rational resource utilization.…”
Section: Discussionmentioning
confidence: 69%